Service availability : principles and practice - Toeroe, Maria; Tam, Francis (Wiley, 2012)
Our society increasingly depends on computer-based systems; the number of applications deployed has increased dramatically in recent years and this trend is accelerating. Many of these applications are expected to provide their services continuously. The Service Availability Forum has recognized this need and developed a set of specifications to help software designers and developers to focus on the value added function of applications, leaving the availability management functions for the middleware. A practical and informative reference for the Service Availability Forum specifications, this.